Diagnostic accuracy of point-of-care natriuretic peptide testing for chronic heart failure in ambulatory care: systematic review and meta-analysis. (21st May 2018) - Taylor, Kathryn S; Verbakel, Jan Y; Feakins, Benjamin G; Price, Christopher P; Perera, Rafael; Bankhead, Clare; Plüddemann, Annette
Abstract: Objective: To assess the diagnostic accuracy of point-of-care natriuretic peptide tests in patients with chronic heart failure, with a focus on the ambulatory care setting. Design: Systematic review and meta-analysis. Data sources: Ovid Medline, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Embase, Health Technology Assessment Database, Science Citation Index, and Conference Proceedings Citation Index until 31 March 2017. Study selection: Eligible studies evaluated point-of-care natriuretic peptide testing (B-type natriuretic peptide (BNP) or N terminal fragment pro B-type natriuretic peptide (NTproBNP)) against any relevant reference standard, including echocardiography, clinical examination, or combinations of these, in humans. Studies were excluded if reported data were insufficient to construct 2×2 tables. No language restrictions were applied. Results: 42 publications of 39 individual studies met the inclusion criteria and 40 publications of 37 studies were included in the analysis. Of the 37 studies, 30 evaluated BNP point-of-care testing and seven evaluated NTproBNP testing. 15 studies were done in ambulatory care settings in populations with a low prevalence of chronic heart failure. Five studies were done in primary care. At thresholds >100 pg/mL, the sensitivity of BNP, measured with the point-of-care index device Triage, was generally high and was 0.95 (95% confidence interval 0.90 to 0.98) at 100 pg/mL. At thresholds <100 pg/mL, sensitivity ranged from 0.46 to 0.97 and specificity from 0.31 to 0.98. Primary care studies that used NTproBNP testing reported a sensitivity of 0.99 (0.57 to 1.00) and specificity of 0.60 (0.44 to 0.74) at 135 pg/mL. No statistically significant difference in diagnostic accuracy was found between point-of-care BNP and NTproBNP tests. Conclusions: Given the lack of studies in primary care, the paucity of NTproBNP data, and potential methodological limitations in these studies, large scale trials in primary care are needed to assess the role of point-of-care natriuretic peptide testing and clarify appropriate thresholds to improve care of patients with suspected or chronic heart failure.